Transformation of Traditional Crimean Tatar Belt Wrestling into a National Sport in the First Decades After the Establishment of Soviet Power in Crimea (1920–1941) - Andrey Mutiyev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The purpose of the article was to study the processes of transformation of belt wrestling as a cultural and historical heritage of the Crimean Tatar people into a kind of national sport in the 1920s – 1941. Material. The research was based on the funds of the State Archives of the Republic of Crimea and newspaper publications from the late 1920s to early 1940s on the development of Crimean Tatar belt wrestling in Crimea. Results. Materials presented in the article highlight the trace of the transition of Crimean Tatars’ national belt wrestling from a form of manifestation of culture and entertainment to a kind of national sport, which became part of the state system of Soviet physical education. In the first decade after the establishment of Soviet power in Crimea, belt wrestling continues to be a part of the national holidays of the Crimean Tatars with the support and participation of the Soviet state administration of physical culture and sports. As a transitional platform for the transformation of belt wrestling from folk fun into a sport was the national Crimean Tatar holidays Derviza, which acquired an all-Crimean character since 1923. Since the late 1920s and early 1930s, the official rules for belt wrestling have been developed, tested, and improved. Wrestling tournaments are separated from national and religious holidays, including in the state system of physical culture events. Until the beginning of the 1940s, the Crimean Tatar wrestling was fully integrated into the system of physical culture work and was included in the new complex “Ready for Labor and Defense” for the Crimea.